Abonos orgánicos y niveles de materia orgánica bajo condiciones de invernadero en Ica, Perú - Beyer Arteaga, Alfredo Alberto (2021)
Organic fertilizers provide important benefits to the soil and therefore to plants, so it is important to evaluate their effects on different crops. In the present study, the effect of seven organic fertilizers and two levels of organic fertilization was evaluated for the variables plant height, dry matter, total nitrogen extraction, total phosphorus extraction and total potassium extraction in Agroceres variety corn as an indicator plant. under greenhouse conditions in Ica, in a completely randomized design. Chicken manure was the best organic source for the variable plant height. Compost treatments were superior for the total nitrogen extraction variable. The manure treatments stood out in the variable total phosphorus extraction. No significant differences were found between organic sources for total potassium extraction or a clear trend for the dry matter variable. Finally, significant differences were found in organic matter levels of 1% and 2% for all the variables under study.